The prevalence and risk of human papillomavirus infection in pregnant women. (25th March 2014) - LIU, P.; XU, L.; SUN, Y.; WANG, Z.
SUMMARY: A series of observational studies were evaluated concerning the risk of human papillomavirus (HPV) infection in pregnancy; however, the results were controversial. We systematically reviewed and collected data on studies regarding HPV prevalence published up to 30 April 2013, in which HPV was detected in pregnant women or both in pregnant and non-pregnant women. In total, 28 eligible studies were included that provided data on HPV infection concerning 13 640 pregnant women. The overall HPV prevalence in pregnant and age-matched non-pregnant women was 16·82% [95% confidence interval (CI) 16·21–17·47] and 12·25% (95% CI 11·50–13·01), respectively. The prevalence in the in three trimesters was 18·20%, 14·38%, and 19·32%, respectively. HPV-16 was the most frequently observed type, with a prevalence of 3·86% (95% CI 3·40–4·32). The overall HPV prevalence varied by study region, age, and HPV type. The meta-analysis showed a significantly increased risk of HPV infection in pregnant women, with a summary odds ratio (OR) of 1·42 (95% CI 1·25–1·61), especially for those aged <25 years (OR 1·79, 95% CI 1·22–2·63). The results suggest that pregnant women, especially those aged <25 years, are more susceptible to HPV infection.